(untitled) (Nexo Revista Científica, 2021)
This paper presents a new circuit of the miniature microwave radiometer for wearable devices, which can be used to monitor the core body temperature (CBT) of internal human tissues continuously 24/7. The measurement results of the proposed device, as opposed to the known miniature wearable radiometers, remain unchanged when the impedance of the examined area varies. We have derived an analytical expression for radiometer measurement error based on parameters of device components. This formula allows accuracies to be estimated and optimal parameters of the circuit to be selected to minimise measurement error at a design stage. It is shown that measurement error is independent of the antenna reflection coefficient and the temperature of the radiometer front-end. A prototype of the single-channel miniature radiometer has 32 х 25 х 14 mm3 dimensions and USB interface communication with PC. A 28-hour run of the device has shown that it is highly stable, and a maximum drift in temperature is 0.15 ̊C. Operating frequency range was 3400-4100 MHz, supply voltage - 5V; power supply of the radiometer in measurement mode is 210 mA; time constant of the radiometer without being averaged is 0.6 sec, at the same time, standard deviation δ = 0.17 ̊С, with further averaging during 4 sec δ=0.052 ̊С, with averaging during 30 sec δ =0.017 ̊C; when there were input reflections R2=0.25, an error in measuring brightness temperature shifted by 0.2 ̊ C; with 10 ̊C variations in ambient temperature the shift was 0.15 ̊C. Introduction of self-contained power supply and wireless communication with smartphone have made it possible to use the proposed radiometer as a wearable device to monitor the temperature of internal tissues and CBT during human activities.